2003
DOI: 10.1086/375538
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Serine/Threonine Kinase 9 Gene Causes Severe X-Linked Infantile Spasms and Mental Retardation

Abstract: X-linked West syndrome, also called "X-linked infantile spasms" (ISSX), is characterized by early-onset generalized seizures, hypsarrhythmia, and mental retardation. Recently, we have shown that the majority of the X-linked families with infantile spasms carry mutations in the aristaless-related homeobox gene (ARX), which maps to the Xp21.3-p22.1 interval, and that the clinical picture in these patients can vary from mild mental retardation to severe ISSX with additional neurological abnormalities. Here, we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
238
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(254 citation statements)
references
References 21 publications
13
238
0
3
Order By: Relevance
“…The most severe phenotype with early-onset encephalopathy was described in the females with the balanced X;autosome translocations, wherein the normal X chromosome was completely inactivated. 46 In our cohort, all females with CDKL5 duplications had random XCI pattern; however, the mothers of male patients 1 and 3 were mildly affected when compared with their sons, and mothers of patients 6 and 7 were healthy, suggesting that their XCI pattern may be different in blood and brain. CDKL5 isoform I, transcribed from exon 1, is expressed in a wide range of brain compartments, including cerebral cortex, hippocampus, cerebellum, striatum, and brain stem, as well as in testes and thymus.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The most severe phenotype with early-onset encephalopathy was described in the females with the balanced X;autosome translocations, wherein the normal X chromosome was completely inactivated. 46 In our cohort, all females with CDKL5 duplications had random XCI pattern; however, the mothers of male patients 1 and 3 were mildly affected when compared with their sons, and mothers of patients 6 and 7 were healthy, suggesting that their XCI pattern may be different in blood and brain. CDKL5 isoform I, transcribed from exon 1, is expressed in a wide range of brain compartments, including cerebral cortex, hippocampus, cerebellum, striatum, and brain stem, as well as in testes and thymus.…”
Section: Discussionmentioning
confidence: 67%
“…12 Conversely, isoform II, transcribed from exons 1a and 1b (but not exon 1), is only expressed at very low levels in human fetal brain and testes. 46,47 It remains to be determined in what brain compartment(s) and in which cells this isoform is predominantly expressed. The phenotypic similarities observed in male patient 5 and female patients 6 and 7 with the duplication of CDKL5 isoform II may result from abnormalities in spatiotemporal functions or interactions of CDKL5 during fetal brain development.…”
Section: Discussionmentioning
confidence: 99%
“…Two splicing variants with distinct 5 0 UTRs have been found: isoform I, containing exon 1, is transcribed in a wide range of tissues, whereas the expression of isoform II, including exons 1a and 1b, is limited to testis and foetal brain. 5,10 Alternative splicing events lead to at least three distinct human protein isoforms. The original CDKL5 transcript generates a long protein of 1030 amino acids (CDKL5 115 ; 115 kDa).…”
Section: Discussionmentioning
confidence: 99%
“…Other research has found that the number of hours of care limits the ability of carers to participate fully in the labour force 5 that, in turn, can lead to financial hardship for those with a child with a disability. 6 The research by Sawyer et al has clear implications for the design of supportive interventions. The focus on time use suggests the value of establishing the threshold above which the demands of caring for a child with a disability puts parents at risk of mental health problems.…”
mentioning
confidence: 99%
“…5 An epileptic encephalopathy associated with abnormalities of the CDKL5 gene was first described in 2003. 6 It was found in children (mostly female) with intellectual disability and infantile spasms, or with a clinical picture resembling earlyonset Rett syndrome. 7 Thus far, no detailed descriptions of the presenting features had been given, and the diagnosis had to be made by screening DNA studies.…”
mentioning
confidence: 99%